If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 15x + 11 = 18x Reorder the terms: 11 + 15x = 18x Solving 11 + 15x = 18x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-18x' to each side of the equation. 11 + 15x + -18x = 18x + -18x Combine like terms: 15x + -18x = -3x 11 + -3x = 18x + -18x Combine like terms: 18x + -18x = 0 11 + -3x = 0 Add '-11' to each side of the equation. 11 + -11 + -3x = 0 + -11 Combine like terms: 11 + -11 = 0 0 + -3x = 0 + -11 -3x = 0 + -11 Combine like terms: 0 + -11 = -11 -3x = -11 Divide each side by '-3'. x = 3.666666667 Simplifying x = 3.666666667
| -5(3x+2)=5 | | -9x+10=-(9x+10) | | z/7=11 | | 5y+3y+8= | | xsquared+4x=7 | | 56-5x-10=112-16x | | 4(x-6)+24=x+29 | | 4(x+24)-6=4x+90 | | 4(x-6)+24=4x+29 | | 4(x-6)+24=4x | | -10=-4a+-7 | | 1/2=0.5 | | -[11(x+2)-10*10]=[10(x-5)+3x](-2)+x | | -.17v-.17=-.11v-.11 | | 8(2k)+7=2k+1 | | (-3x^2-8+5)+(x^2-6x+2)= | | 6x+23=11x-2 | | 2(2x-5)=18 | | 11x+2=5x+56 | | 5x+9-2x+4+7y= | | 4x+33=3x+24 | | .167(z+3)=-.5(z+2) | | (y-8)-(y+8)=6y | | 2x/15=4/5 | | (x+3)(sx+5)=7 | | 34-4x=10-10x | | y^2+5xy=3x^3 | | v+.83v-.17=.375(v+.67) | | 1/14(196x-98)=156 | | 7v-28=-7v | | 2(8+2x)=96 | | 3n^2-13n-63=-7 |